Development of Augmented Reality Flash Card Learning Media On Building Space Materials for Elementary School Students - Ragil Bagus Cahya Permata; Via Yustitia (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2026)
Learning about building space at the elementary school level still requires tools that can help students understand concepts in a real and visual way, so that they can strengthen their understanding of numeracy. This study aims to explain the process of developing Flash Card learning tools supported by Augmented Reality in building materials in grade V elementary schools, assess the level of media feasibility based on assessments from material experts and media experts, and evaluate the level of media practicality based on student responses. This research uses the Research and Development (R&D) method with a 4D development model (Define, design, Develop, and Disseminate), and involves subjects in the form of teachers and grade V students. The results of the study show that this media is very suitable for use with a validation rate of material experts reaching 89% and media experts reaching 86%. The level of practicality also showed very positive results based on responses from students in the small group of 90.5% and the large group of 88.61%. The conclusion of this study is that Flash Card media supported by Augmented Reality is very feasible and practical to be used as a means of learning in improving students' spatial visualization interactively.